2020
DOI: 10.1126/scisignal.aaw7963
|View full text |Cite
|
Sign up to set email alerts
|

Local Ca 2+ signals couple activation of TRPV1 and ANO1 sensory ion channels

Abstract: ANO1 (TMEM16A) is a Ca2+-activated Cl− channel (CaCC) expressed in peripheral somatosensory neurons that are activated by painful (noxious) stimuli. These neurons also express the Ca2+-permeable channel and noxious heat sensor TRPV1, which can activate ANO1. Here, we revealed an intricate mechanism of TRPV1-ANO1 channel coupling in rat dorsal root ganglion (DRG) neurons. Simultaneous optical monitoring of CaCC activity and Ca2+ dynamics revealed that the TRPV1 ligand capsaicin activated CaCCs. However, depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 74 publications
2
38
0
Order By: Relevance
“…4i, j ). Thus, Ca 2+ release and SOCE are coupled and are augmented by deletion of Pkd1 , probably due to upregulation of TMEM16A 23 , 25 27 . SOCE is potently blocked by the inhibitors of Orai channels and transient receptor potential (Trp) channels, YM58483 and SK&F96365, respectively, suggesting a contribution of both channels to enhanced SOCE in Pkd1 −/− cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4i, j ). Thus, Ca 2+ release and SOCE are coupled and are augmented by deletion of Pkd1 , probably due to upregulation of TMEM16A 23 , 25 27 . SOCE is potently blocked by the inhibitors of Orai channels and transient receptor potential (Trp) channels, YM58483 and SK&F96365, respectively, suggesting a contribution of both channels to enhanced SOCE in Pkd1 −/− cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the TRPV1-ANO1 coupling led to enhanced action potential firing in response to CAP, a response that was also blocked by the ANO1 blocker T16 Inh -A01. Shah et al [ 218 ] reported a similar interaction between TRPV1 and ANO1 in peripheral somatosensory neurons. They also showed that the CAP-induced ANO1 conductance involved ER Ca 2+ release through an additional interaction with type 1 IP 3 R (IP 3 R1).…”
Section: Regulation Through Coupling Of Ano1 With Other Membrane Proteinsmentioning
confidence: 91%
“…The fluorescence of EYFP-QL is quenched by iodide and since Clchannels (e.g. GABAA) are permeable to this anion, EYFP-QL fluorescence quenching by Ican be used to monitor Clchannel activation (40)(41)(42)(43). We co-cultured these 'GABA indicator' HEK293 cells with DRG neurons and measured EYFP-QL fluorescence quenching induced by the addition of 5 mM NaI to the extracellular solution (Fig.…”
Section: Transplantation Of Forebrain Gabaergic Neuron Precursors Into the Adult Mouse Drg In Vivo Delivers An Analgesic Mechanismmentioning
confidence: 99%